A chain of tools: An experimental study on picks of the Qinling region. (2nd May 2016) - Chen, Sheng-qian; Chen, Wei-ju
Abstract: Picks are a common lithic tool in the Qinling region, where an Acheulean-like industrial complex dominated during the early Paleolithic. They are assumed to be manufactured by the technology of direct percussion flaking. This experimental study indicates that the trihedral points of picks cannot be produced by this technology, but are produced by throwing. The benefit of using the method is not only to obtain trihedral blanks, but also includes producing blanks of other tools such as cleavers, handaxes, knives, and choppers. These products are different components of a whole chaine d'operatoire for stone tool production. Participation in the experiment by both males and females suggests that the latter can also use the method of throwing to produce all these blanks, although there are some differences in the mass of cobble used and throwing power. As females are able to produce heavy tools like picks, there is no reason to assume that heavy tools were made only by males, in particular, for the purpose of sexual symbols.